Exploratory study on gaming technology perception by children in rural area / Wan Nor Aina Wan Manso - Wan Manso, Wan Nor Aina (2013)
Children in this era are said to be IT literate. Despite the fact that today's children have many chances to interact with IT technology, what they understand about technology from their point of view still needs to be explored. This research expands the study done by Salleh (2012) in her thesis titled "Children's perception on gaming technology" to rural area children as participant. The same method in Salleh's thesis which includes questionnaire, interview and drawing session will be replicated with different sets of participant and setting. This research explores the rural area children's gaming perception such as their IT knowledge, experience and emotional response towards gaming technology. Moreover, participatory design session is also conducted to identify the gaming technology features desired by the children in rural area. Lastly the comparison between urban and rural area children perception are analyzed. From the study, it is found that lifestyle, technology adoption, IT knowledge and creativity differentiate urban children and rural children gaming perception. However, both area children preferred the same feature which is interactive and colorfully designed technology devices. These findings will be useful to the technology and gaming developers in making their decision in developing the gaming devices that are usable and yet it is coming with the fun experiences for children and young peoples.